Seafood Knowledge, Perceptions, and Use Patterns in Florida: Findings from a 2013 Survey of Florida Residents - Lisa Krimsky; Charles Adams; Bryan Fluech (EDIS, 2015)
Over the past few years, consumers have begun to pay more attention to the nutritional benefits, sustainability, and environmental impact of consuming seafood. However, media coverage of these concerns may leave consumers confused and uncertain about how they should incorporate seafood into their diets. In 2013, a survey was conducted to better understand Florida seafood consumer preferences, perceptions, and concerns. This 4-page fact sheet explains the survey’s findings and how they might help Extension deliver effective seafood-based education to Florida residents. Written by Lisa Krimsky, Charles Adams, and Bryan Fluech, and published by the UF Department of Food and Resource Economics, May 2015.